Politicizing the future: on lithium exploration in Portugal - Araújo, Emília Rodrigues (2022)
This text explores the meaning of the expression "mined future," which has been used by local populations who oppose lithium production in Northern Portugal. We argue that the expression encapsulates the existence of a conflict for the "ownership" of future, unfolding a battle of visions of the future between local populations and governments. The local population sees the exploitation of lithium as a takeover of future. In contrast, the governments justify the project by promising a sociotechnical future in convergence with European green energy rhetoric. This article follows a grounded theory approach. It relies on information collected about the lithium exploration in Portugal, mainly through journalistic pieces and opinion articles disseminated between 2019 and 2020. In particular, the paper proposes that political action that involves large sociotechnical ventures with the potential of contamination needs to consider the local collective perceptions of the future.